ALâ€“GHAZÄ€LÄª: MENDAMAIKAN SYARÄªâ€™AH DAN TASAWWUF - Sulaeman, Mubaidi (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2020)
This article describes al-GhazÃ„ÂlÃ„Â«Ã¢â‚¬â„¢s thoughts about Sufism which became a synthesis of philosophical considered extreme tasawwuf and literal and rigid Islamic jurisprudence. This paper argued that Al-GhazÃ„ÂlÃ„Â« attempted to mediate the situation of religion among Muslims who messed up because of tasawuf deviating from the principal teachings of Islam and Islamic jurisprudence and being used by the authorities as a measure to punish the Sufis categorically without considering the truth of their teachings. In his IÃ¡Â¸Â¥yÃ„Â Ã¢â‚¬ËœUlÃ…Â«mudÃ„Â«n, al-GhazÃ„ÂlÃ„Â« leans to his biggest thoughts about SunniÃ¢â‚¬â„¢s Sufism. It teaches theology such as tawÃ¡Â¸Â¥Ã„Â«d, makhÃ„Âfah, maÃ¡Â¸Â¥abbah and maÃ¢â‚¬â„¢rifah, from which the concepts of tawbah, Ã¡Â¹Â£abr, tawakkal, zuÃ¡Â¸Â¥Ã…Â«d and riÃ¡Â¸Âa came from. This article found that al-GhazÃ„ÂlÃ„Â«Ã¢â‚¬â„¢s sufism is closer to practical tasawuf , which is built upon the QurÃ¢â‚¬â„¢Ã„Ân and the Ã¡Â¸Â¤adÃ„Â«th. al-GhazÃ„ÂlÃ„Â« also wrote his personal experience in his masterpiece.Keywords: Tasawuf, Islamic Jurisprudence, al-GhazÃ„ÂlÃ„Â«